Charles Darwin And The Oldest Glacial Events In Patagonia: The Erratic Blocks Of The Río Santa Cruz Valley - Malagnino, Eduardo Cayetano (2009)
Although the depositational environment assigned by Darwin to the large erratic blocks and gravels in the Río Santa Cruz valley has been reinterpreted, his geomorphological and stratigraphic observations are still in force. The large erratic blocks he described as crowning the Condor Cliff terrace and spread at the bottom of the valley just east of this locality (Sites 2 and 3), are now interpreted as indicators of the maximum glacial expansion in Patagonia. Similar blocks, though of a different lithology, accumulated over a lower terrace located up-valley (Site 4), are now linked to moraines and glacifluvial terraces of the Penultimate Glaciation. Finally, in addition to the erratic block discovered by Darwin in the lower Río Santa Cruz valley (Site 1), there are others - recently discovered - which probably account for a catastrophic event ascribed to a big glacier-lake outburst during the last interglacial.